Using the optimal seed germination temperature approach to determine the potential distribution of Inga jinicuil in Mexico under climate change scenarios - Salvador Sampayo-Maldonado; Daniel Cabrera-Santos; Patricia Dávila-Aranda; Norma Isela Rodríguez-Arévalo; Alma Orozco-Segovia; Maraeva Gianella; Elizabeth Bell; Michael Way; Robert H. Manson; Gabina S. Quintas; Cesar M. Flores-Ortíz; Tiziana Ulian (Scientific Reports)
Abstract Inga jinicuil is used extensively in shade coffee farms in Mexico, a diversified agroforestry system providing important environmental goods and services. However, its recalcitrant seeds represent an important barrier to its propagation. Given the climate change scenarios, it will be necessary to generate information on the effect of temperature on germination, a key stage for the establishment and conservation of the species. The objective of the study was to determine the optimal germination temperatures for I. jinicuil using linear and non-linear models, as well as the species’ potential distribution under contrasting climate change scenarios using the GISS-E2-1-G model. Seeds were placed in germination chambers at constant temperatures of 5 ± 0.5 to 40 ± 0.5 °C, and their thermal responses were then modelled using a thermal timing approach. Results indicated a good fit of models of I. jinicuil germination in response to temperature. Seeds germinated across a wide temperature range; the base temperature for germination was in the range of 4.8 to 9.45 °C (average Tb: 6.21 ± 2.23 °C). and the ceiling temperature in the range of 44.51 to 49.20 °C (average Tc: 47.6 ± 2.73 °C). While the optimal temperature was found in the range of 29.58 to 33.02 °C (average To: 31.52 ± 1.43 °C). The suboptimal thermal time ( $$\:θ\:$$ 1(50)) for germination of 50% of the seed lot was 117.164 ± 0.636°Cd, which under current climatic conditions is reached in 6.6 days. According to climate modeling, the distribution of I. jinicuil populations will decrease by up to 23% in the future relative to the current distribution. Results indicate that high temperatures have a negative effect on germination, which may be related to seed physiology. More research on seed germination and growth is needed to improve the management and conservation of this species and its continued use as a shade tree in coffee agroforestry systems.